2012
DOI: 10.1063/1.4766677
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between collective behavior and spreading dynamics on complex networks

Abstract: There are certain correlations between collective behavior and spreading dynamics on some real complex networks. Based on the dynamical characteristics and traditional physical models, we construct several new bidirectional network models of spreading phenomena. By theoretical and numerical analysis of these models, we find that the collective behavior can inhibit spreading behavior, but, conversely, this spreading behavior can accelerate collective behavior. The spread threshold of spreading network is obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Without loss of generality, the topological structure of deterministic network G is characterized by WS small-world network 29 or BA network. 30 The WS network is generated with probability 0.1 for rewiring links, where each node is symmetrically connected with its six nearest neighbors in its initial nearest-neighbor network.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Without loss of generality, the topological structure of deterministic network G is characterized by WS small-world network 29 or BA network. 30 The WS network is generated with probability 0.1 for rewiring links, where each node is symmetrically connected with its six nearest neighbors in its initial nearest-neighbor network.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In [31], authors considered adaptive mechanism between dynamical synchronization and epidemic spreading behavior on complex networks, in which two models of epidemic synchronization were introduced for the first time to analyze the stability of epidemic synchronization and obtained local and global conditions. Following that, the interplay between collective behavior and spreading dynamics on complex networks was further investigated in [32], where several bidirectional networks models of spreading phenomena were constructed, and found that the collective behavior and spreading behavior are influenced each other. But the models in the above two papers are all based on the heterogeneous mean-field theory.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Unfortunately, little work is devoted to the study of synchronization during epidemic spread. 8,17 Li et al 8 proposed the models of SIS (susceptible-infected-susceptible) and SIR (susceptible-infected-recovered) epidemic synchronization based on heterogeneous mean-field (HMF) theory and studied the dynamics of SIS epidemic synchronization. Li et al 17 also investigated the interplay between collective behaviors and spreading dynamics on complex networks and analyzed the control problem of spreading behaviors.…”
Section: Introductionmentioning
confidence: 99%